STUDI PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO DI DESA TINGKEM - Abdul Syafi; Khairullah Yusuf; Joni Arfiandi (Malikussaleh Journal of Mechanical Science Technology, 2022)
Micro Hydro Power Plant (PLTMH) is a small-scale power plant with an installed capacity of under 200 kW that uses water flow from irrigation channels, rivers, or natural waterfalls by utilizing potential waterfalls at the proposed site. This study discusses the planning and equipment needed for the PLTMH located in a rural area such as Tingkem Village to meet the electricity needs of local residents. The research also includes the technical feasibility study aspect by surveying the hydrological potential and the height of the waterfall at the proposed site. Based on the study, the electricity needs of the residents of Tingkem Village at a peak load of 20kW. The results of the survey show that the potential of water discharge in the Aih Tilis river in Tingkem Village is about 0.95 m3/s with a flow discharge designed of 0.38 m3/s and has a head of about 7.5 m so that it can generate a power of 28 kW which is sufficient to meet the needs of local residents. Based on the head, discharge plan and installed capacity, the appropriate turbine type is a cross-flow type and the generator type is the synchronous generator type. Based on the findings, it can be said that the PLTMH is suitable to be developed in the Tingkem Village.